2023
DOI: 10.1136/bmjopen-2022-068554
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between daytime napping with the occurrence and development of diabetes: a systematic review and meta-analysis

Mengdie Liu,
Minhui Liu,
Shuo Wang
et al.

Abstract: ObjectiveTo determine the relationship of napping with incident diabetes risk and glycaemic control in people with diabetes.DesignSystematic review and meta-analysis.Data sourcesMEDLINE (PubMed), EMBASE, Web of Science and the Cochrane Library were searched for studies published from database inception to 9 May 2023.Eligibility criteriaObservational studies reporting the relationship of napping with diabetes or glycaemic control in patients with diabetes in adult populations were included.Data extraction and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 63 publications
(209 reference statements)
0
3
0
Order By: Relevance
“…Previous meta-analyses investigated the association between napping and T2DM, but these studies primarily focused on simplistic dichotomous classifications of either napping or no napping, or nap duration ≥1 hour/<1 hour ( 13 15 ). A recent meta-analysis examining specific nap durations (<30 minutes, 30-60 minutes, >60 minutes) revealed that naps exceeding 30 minutes were significantly associated with an increased risk of developing T2DM ( 16 ). However, these studies failed to provide a robust argument for the influence of nap duration on T2DM risk.…”
Section: Introductionmentioning
confidence: 99%
“…Previous meta-analyses investigated the association between napping and T2DM, but these studies primarily focused on simplistic dichotomous classifications of either napping or no napping, or nap duration ≥1 hour/<1 hour ( 13 15 ). A recent meta-analysis examining specific nap durations (<30 minutes, 30-60 minutes, >60 minutes) revealed that naps exceeding 30 minutes were significantly associated with an increased risk of developing T2DM ( 16 ). However, these studies failed to provide a robust argument for the influence of nap duration on T2DM risk.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with non-nappers, people with regular napping were 1.3 times more likely to have poor glycemic control (N=12,997) (aged 59 years, 38% females) ( 49 ). Based on a recent meta-analysis, compared with non-nappers, nappers had a 20% increased risks of developing T2D ( 50 ). How napping frequency affect glucose metabolism has not been clear.…”
Section: Discussionmentioning
confidence: 99%
“…Because midday naps could modify such associations, the researchers have been paying much more attention to napping behavior than ever. While it has been consistently reported that midday naps, especially if it is long (>1h), could be associated with higher risk of diabetes ( 3 , 4 ), previous findings about influence of midday naps on glycemic control are conflicting ( 5 ).…”
mentioning
confidence: 99%